Phenolic compounds in cork used for production of wine stoppers as affected by storage and boiling of cork slabs - Mazzoleni, V; Caldentey, P; Silva, A (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 1998)
Phenolic compounds (benzoic and cinnamic acid derivatives, vanillin, syringaldehyde and acetovanillone) were identified in cork used for production of wine stoppers by extraction in an ethanolic solution and by HPLC analysis. The effect of storage and boiling of cork slabs on these compounds were investigated. In each sample, cinnamic acids and vanillin have predominated among phenolics. Boiled cork was significantly different from raw slabs in the concentration of protocatechuic, caffeic, p-coumaric acids, and vanillin. The significant differences between cork from stored and from unstored slabs were evident in protocatechuic, 4-hydroxybenzoic, caffeic, and ferulic acids. Storage of slabs increased the amount of extractable cinnamic acids. On the other hand, boiling decreased the concentration of the same phenolic acids and increased that of vanillin. Boiling after storage can be beneficial to the cork quality, reducing the amount of potentially negative flavor compounds (cinnamic acids) and increasing potentially positive flavor compounds (vanillin).
Keywords: Cork; phenolic compounds; processing of cork slabs